The role of local sustainable agri-food systems in enhancing the resourcefulness and well-being of communities – experiences from the Portuguese Oeste region - Luís, Duarte (2022)
This communication aims to present a PhD research project in its early stage. It intends therefore on discussing the main questions posed, the main goals established, and the main methodologies foreseen in order to foment a debate about its merits and in this way allow further improvements to be made while still in the designing phase of the research. The research project here presented aims to shed light on current sustainable farming practices that are established around alternative agri-food systems and to analyze how these practices (re)connect to the territory. In other words, it aims to help understand how these environmentally friendly farming practices interact with their socio-economic and cultural contexts, and how can local communities benefit from their presence. It should be pointed out that the existing literature examining the “empirical foundations for place-based agriculture” is scarce (Chapman et al., 2017). And on the other hand, sustainable farming practices’ studies are most frequently focused either on the biotechnical functioning of the systems or on the social-political movements they represent, but “they do not explicitly consider how farming systems interact with their socio-economic environment” (Therond et al., 2017). Regarding the methodology, a mixed methods research strategy is envisaged, integrating both qualitative and quantitative methods but still keeping a focus on inductive and interpretative approaches. Being the main goal of this research to expand the current understanding of the territorial integration of agroecological practices, a case-study instrument, supported by personal interviews, will be used. Later, an action-research method will be applied in order to debate and prioritize the most relevant activities that could be undertaken toward an agroecological transition. Outcomes are expected in the form of governance guides for decision-makers and practitioners, and for academia, in the form of scientific research papers providing a deeper understanding of the territorial integration of alternative sustainable farming practices.